2008
DOI: 10.1136/bmj.a2656
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of Alexander technique lessons, exercise, and massage (ATEAM) for chronic and recurrent back pain: economic evaluation

Abstract: Objective An economic evaluation of therapeutic massage, exercise, and lessons in the Alexander technique for treating persistent back pain.Design Cost consequences study and cost effectiveness analysis at 12 month follow-up of a factorial randomised controlled trial.Participants 579 patients with chronic or recurrent low back pain recruited from primary care.Interventions Normal care (control), massage, and six or 24 lessons in the Alexander technique. Half of each group were randomised to a prescription for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 16 publications
2
79
1
Order By: Relevance
“…Furthermore, some studies included funder costs only, 17,[21][22][23][24][25][26] while others presented societal perspectives that also included costs to the participant. 11,[18][19][20]27 Consequently, there was a wide variation in costs per QALY gained between the studies. For example, the study of Gusi et al, involving a walking programme for older women who were overweight or had moderate depression, had the lowest cost per QALY of €348.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies included funder costs only, 17,[21][22][23][24][25][26] while others presented societal perspectives that also included costs to the participant. 11,[18][19][20]27 Consequently, there was a wide variation in costs per QALY gained between the studies. For example, the study of Gusi et al, involving a walking programme for older women who were overweight or had moderate depression, had the lowest cost per QALY of €348.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…When considering interventions for specific disease-based populations, the exercise prescription given by the GP and exercise counselling by the practice nurse for people with chronic or recurrent low back pain 20 was more cost-effective (€4577 per QALY) than the water-based exercise intervention for older participants with osteoarthritis of the hip and/or knee (€9160 per QALY). 18 A weekly exercise class for sedentary people aged 65 years and older 24 was more cost-effective (€19 425 per QALY) than both the supervised gym-based exercise classes and the instructor-led walking programme for sedentary 40-74 year olds (€35 665 and €86 877 per QALY).…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…Ratcliffe et al [37] showed that acupuncture had a low ICER compared to GP care from the healthcare sector perspective (4,241 in 2002 to 2003 GBP per QALY gained, 95% CI = 191-28,026), and was dominant over GP care from the societal perspective. Hollinghurst et al [34] investigated the cost-effectiveness of massage over a 1-year period. Compared to GP care, massage incurred higher costs from the healthcare sector's perspective and was less effective (QALY gained = -34,473 in 2005 GBP).…”
Section: Quality Of the Economic Evaluationmentioning
confidence: 99%
“…The only exceptions were two studies which recruited participants of a mixed duration of symptoms [30,32] two which did not specify the duration of symptoms [20], and one which recruited participants sick listed for less than 2 weeks due to LBP [31]. Most studies were conducted in the UK [32][33][34][35][36][37][38][39][40] or other European countries [21-24, 26-29, 31, 41-45]; three studies were conducted in the United States [20,30] and two in Canada [25,46]. All studies were published in English.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation